2018
DOI: 10.1186/s41232-017-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating plasma microRNA profiling in patients with polymyositis/dermatomyositis before and after treatment: miRNA may be associated with polymyositis/dermatomyositis

Abstract: BackgroundMicroRNAs (miRNAs) are involved in the regulation of key biological processes and have been implicated in various diseases, including autoimmune disorders. The pathogenesis of polymyositis (PM) and dermatomyositis (DM) is considered to be mediated by autoimmune reactions. To determine miRNA role in the development and progression of PM and DM, we performed plasma miRNA profiling in PM/DM patients before and after treatment.MethodsTotal RNA was isolated from plasma of 10 patients before and after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“… [ 257 ] miRNA Plasma levels of hsa-miR-4442 in active PM and DM are very high. [ 258 ] miR-206 is decreased in DM patients. It is necessary for differentiation and maintenance of adult skeletal muscle.…”
Section: Epigenetic Factorsmentioning
confidence: 99%
“… [ 257 ] miRNA Plasma levels of hsa-miR-4442 in active PM and DM are very high. [ 258 ] miR-206 is decreased in DM patients. It is necessary for differentiation and maintenance of adult skeletal muscle.…”
Section: Epigenetic Factorsmentioning
confidence: 99%
“…There were several studies which investigated the correlations between serum microRNAs and clinical phenotypes in DM patients (Table 3) [8, 11, 23–25]. Inoue and colleagues suggested that the serum and the skin expression of miR-233 were both downregulated in DM patients with Gottron's papules and clinically amyopathic DM patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic roles of microRNAs have been extensively investigated in malignant diseases as well as in autoimmune disorders. Although many microRNAs levels altered in PM/DM patients after treatment, little study reported the role of microRNA in PM/DM (8). So far, miR-21, miR-381, and miR-146a have been reported to regulate macrophage migration in PM/DM (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%